Active power control strategy of wind farm considering fatigue load of wind turbines. (November 2021) - Zhao, Jie; Fang, Yudi; He, Yuqin; Fang, Junjun; Wen, Libin; Liang, Yilin; Xiao, Siyi
Abstract: For the purpose of maximize the utilization of wind energy and reduce the generation cost of wind farms, an active power control strategy of wind farm considering the fatigue load intensity of wind turbines was proposed. Turbulence intensity, average wind speed and active power command were used to evaluate the comprehensive fatigue load strength of the wind turbine. Then an improved particle swarm optimization algorithm was applied to optimize the active power distribution of each wind turbine, which maximize wind energy capture and keep the fatigue load intensity of each wind turbine within a certain allowable range. The effectiveness is proved by the analysis of an example. The results show that the control strategy is helpful to reduce the fatigue load intensity and reduce the operation and maintenance of the WF and the cost of power generation, which can improve the economy of the power system.